Geoecological aspects of spring water forming in Sergiev Posad region (Moscow region) - E U Vasilieva; A A Rasskazov (RUDN Journal of Ecology and Life Safety, 2009)
In article the results of the research work of series of springs are stated. Regularity of change of spring water quality under the influence of man-caused factors is revealed. Such factors as geological structure of rocks, sorption characteristics, presence of trees plantations etc., are very important for prevention of spring water pollution.